Addressing perceptions of opiate-using prisoners to take-home naloxone: findings from one English region. Issue 2 (6th June 2016) - Sondhi, Arun Charles
Abstract : Purpose: – The purpose of this paper is to understand prisoner perceptions on being trained and having received take-home naloxone (THN) kits once released from prison back into the community, in order to prevent an opiate-related overdose. Design/methodology/approach: – A survey was run of all prisoners receiving THN training across ten prisons in one English region. In total, 142 prisoners were surveyed out of 206 (69 per cent) being trained in THN across the ten prisons. Five focus groups ( n =26) with prisoners were conducted across four remand and one open prison that included discussions on THN within a range of topics. Discussions were recorded using short-hand and the data were subsequently thematically interpreted using visual mapping techniques. Findings: – The survey highlighted a high degree of exposure amongst prisoners to overdose either directly (54 per cent) or having witnessed another person's overdose (73 per cent). For prisoners who had overdosed, only a minority (38 per cent) were taken to hospital by an ambulance. In total, 81 per cent of prisoners surveyed also expressed little or no knowledge about THN prior to training. Prisoners were resistant to THN as an intervention resulting from this lack of prior knowledge. Focus group interviews suggested that there was a confused and mixed message in providing a harm reduction initiative within the context of recovery-orientated treatment. Prisoners also exhibited name confusion with other drugs (naltrexone) and there was some degree of resistance to being trained based on perceived side-effects brought on by its administration. Prisoners were also acutely aware of official agency perceptions (e.g. police) if seen to be in possession of THN kits. Practical implications: – The distribution of THN within a custodial setting requires consideration of wider marketing approaches to address levels of confusion and misapprehension amongst prisoners. Originality/value: – The study is one of the few focused on THN based on a UK prison environment.